Clinical and dermoscopic characteristics of new naevi in adults: results from a cohort study. (10th October 2013) - Oliveria, S.A.; Yagerman, S.E.; Jaimes, N.; Goodwin, A.I.; Dusza, S.W.; Halpern, A.C.; Marghoob, A.A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Naevogenesis is a dynamic process that occurs throughout life. Adults develop comparatively fewer new naevi than children. Naevi tend to maintain their dermoscopic morphology. What does this study add? The dermoscopic morphology of new naevi in adults. The rate of new naevus formation in adults. Support to the theory of a dual concept of naevogenesis.